Police and Transgender and Gender Diverse People in the United States: A Brief Note on Interaction, Harassment, and Violence. Issue 23 (December 2022) - Stenersen, Madeline R.; Thomas, Kathryn; McKee, Sherry
Transgender and gender diverse (TGD) people in the United States continue to face dire rates of police violence and harassment. However, little research has examined this phenomenon using large-scale nationwide data. The current study utilized data from the United States Transgender Survey to examine the prevalence and correlates of police interaction, harassment, and violence among TGD people in the United States. Police harassment and violence types examined included reported incidences of (a) officers using the wrong pronouns, (b) officers asking about an individual's transition, (c) verbal harassment, (d) physical attack, (e) forcing sex to avoid arrest, and (f) unwanted sexual contact from an officer. Results from a weighted sample of 22, 456 TGD people revealed that 40.3% reported having interacted with the police in the past year. Among those who interacted with the police in the past year, 45.7% reported experiencing at least one incident of police verbal harassment and 6.1% reported at least one incidence of police physical/sexual violence in the past year. Engaging in sex work was one of the most consistent predictors of police interaction, harassment, and violence. Notably, sex workers were approximately 11 times more likely to report being forced to engage in sex with the police to avoid arrest when compared to non-sex workers. Overall, people of color also reported significantly higher rates of police harassment and violence compared to their White counterparts. Additional correlates included income, educational attainment, and participation in other illegal work. Taken together, the findings of the current study highlight the urgent need for additional examination, intervention, and advocacy to eliminate police harassment and violence against members of the TGD community in the United States.